1991
DOI: 10.1055/s-2007-1002646
|View full text |Cite
|
Sign up to set email alerts
|

Induction and Possible Role of Fibrinolysis in Diabetes Mellitus

Abstract: This article reviews the evidence supporting a relationship between an enhanced tissue injury, increased fibrin formation, defective fibrinolysis, and the evolution of the complications of late diabetic disease. Particular attention is drawn to the role of a defective endothelial cell mediated fibrinolysis with respect to increased fibrin formation and a delayed tissue repair in diabetic patients. Reviewed are studies that indicate that it is possible in patients with diabetes by means of sulfonylurea compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The contribution of fibrinolytic system abnormalities to the development of diabetic micro-and macrovascular complications is still controversial [15]. In several studies activity of the fibrinolytic system in diabetics was found to be increased [16][17][18], decreased [19][20][21] or unchanged [22].…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of fibrinolytic system abnormalities to the development of diabetic micro-and macrovascular complications is still controversial [15]. In several studies activity of the fibrinolytic system in diabetics was found to be increased [16][17][18], decreased [19][20][21] or unchanged [22].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, there is evidence that SU might increase tissue plasminogen activator production by endothelial cells and inhibit platelet function, two mechanisms that would likely prove to be beneficial at the acute stage of myocardial infarction [1,27].…”
Section: Representativeness Of the Study Populationmentioning
confidence: 99%